Characteristic Quality of Pinrang’s Cocoa Beans During Fermentation Used Styrofoam Containers - Erina Septianti; Salengke; Jumriah Langkong; Nandi K. Sukendar; Arini Putri Hanifa (Hasanuddin University Food Science and Technology Study Program, 2020)
Pinrang Regency is one of the regencies that contributes the largest production in South Sulawesi. The fermentation process is the stage of processing cocoa beans that must be carried out to guarantee the taste and aroma of good chocolate. The purpose of research is to study the effect of fermentation time with different cocoa clones on the quality characteristics of cocoa beans during fermentation. Characterization was held by observing the shape and color of the cocoa beans visually and measuring the temperature, pH, total acid, water content and fat content of the beans during fermentation. The results was showed that cocoa beans from local clones were better than Sulawesi 2 clones based on the quality characteristics of the beans produced. The best beans quality is on the 4 and 5 days of fermentation which produces an optimum temperature of around 45-47°C, pH around 5-5.4, total acid around 0.90%. Cocoa beans with a physical appearance and color that is bright enough, fat content around 50.45 %, and the water content is quite low around 4.97%. The quality of the cocoa beans produced is still in accordance with SNI 2323-2008. The use of styrofoam can be used as an alternative besides fermentation with wooden boxes that are usually done by farmers. The results of the study are expected to be used to obtain data and information on the characteristics of fermented cocoa beans, especially from Pinrang Regency, South Sulawesi.